Therapeutic and Analgesic Efficacy of Laser in Conjunction With Pharmaceutical Therapy for Trigeminal Neuralgia - Ebrahimi, Hooman; Najafi, Shamsolmoulouk; Khayamzadeh, Mina; zahedi, Amirabbas; Mahdavi, Atossa (Journal of Lasers in Medical Sciences, 2017)
Introduction: Trigeminal neuralgia (TN) is the most common neuralgia in the head and neck region and a common cause of orofacial pain. It is routinely treated with carbamazepine. Laser, acupuncture and radiofrequency are among other treatment modalities for this condition. This study sought to assess the efficacy of laser therapy in conjunction with carbamazepine for treatment of TN. Methods: A total of 30 patients who met the inclusion criteria were divided into 2 groups of cases and controls (n = 15) by double blind randomized controlled clinical trial. All patients received 100 mg carbamazepine at baseline and another 100 mg after 2 days for pain control. In the case group, low level laser therapy (LLLT) was also performed in addition to pharmaceutical therapy. Sham laser was used in the control group instead of LLLT. Treatment was continued for 9 sessions (3 days a week). The intensity of pain was measured and compared in the 2 groups using visual analog scale (VAS) in 3 period. The qualitative variables among the groups were compared using the repeated measures analysis of variance (ANOVA). Results: The severity of pain was lower at the end of treatment in the case compared to the control group so this difference was statistically significant (P = 0.003). The severity of pain decreased in both groups over time. Significant difference was noted in this regard between the 2 groups either (P = 0.003). At the end of treatment pain intensity dropped in the intervention group from 6/8 to 1/2 and control group from 6/6 to 2/7. Conclusion: Laser therapy did add to the value of pharmaceutical therapy for treatment of TN. Both groups experienced significant improvement over time. So it is better to used laser complementary therapy to reduce side effects and the medicine dosage.